Automatic extraction of 12 cardiovascular concepts from German discharge letters using pre-trained language models: $hPhillip Richter-Pechanski, Nicolas A Geis, Christina Kiriakou, Dominic M Schwab and Christoph Dieterich - Richter-Pechanski, Phillip; Geis, Nicolas; Kiriakou, Christina; Schwab, Dominic Mathias; Dieterich, Christoph (Digital health, 2021)
Objective A vast amount of medical data is still stored in unstructured text documents. We present an automated method of information extraction from German uns...